Using POSS–C60 giant molecules as a novel compatibilizer for PS/PMMA polymer blends. Issue 23 (15th February 2016) - Han, Di; Zhang, Qin; Chen, Feng; Fu, Qiang
Abstract : Janus POSS–C60 (JPC) as a novel compatibilizer. Abstract : Herein, we report a novel strategy to use Janus polyhedral oligomeric silsesquioxane (POSS)–[60]fullerene (C60 ) (JPC) giant molecules as compatibilizer for immiscible polystyrene (PS)/polymethyl methacrylate (PMMA) blends. It was found that the domain sizes of the dispersed PMMA phase decrease in PS matrix, and tensile strength and elongation of PS/PMMA blends were largely enhanced by adding a small amount of JPC. More importantly, both interfacial tension analyses and elemental Si distribution in the blends suggest a possible location of the JPC at the PS/PMMA interfaces. Our studies provide not only a new idea for the compatibilization of polymer blends, but also for precisely controlling the positions of nanoparticles in a polymer matrix, which is also of great importance for the preparation of polymer nanocomposites with high-performance and excellent functionality.